2011
DOI: 10.2298/avb1106531s
|View full text |Cite
|
Sign up to set email alerts
|

The influence of dietary zinc content on mechanical properties of chicken tibiotarsal bone

Abstract: The authors evaluated the effect of diets with different Zn levels on mechanical properties of bones in 60 Ross 308 hybrid broilers, from 2 to 35 days of age, which were randomly divided in 2 groups, with 30 chickens each. The first group (Zn50) was fed a commercial basal diet with no Zn additives (zinc content - 50 mg/kg feed). The second group (Zn100) was fed the basal diet + 50 mg of Zn/kg feed. In this group the dietary Zn level was increased by adding 62.23 mg of zinc oxide (ZnO)/kg feed to starter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
3
3
0
Order By: Relevance
“…However, the increase of the ultimate strength was the same in both groups of chickens fed low-Zn diet irrespective of phytase inclusion. Our results agree with others, who report an influence of dietary Zn on the mechanical properties of bones [ 49 51 ]. On the other hand, there are studies showing that low-Zn diets do not increase bone breaking strength when compared to the Zn-deprived control [ 8 , 21 , 52 ] or group supplemented with ZnO at recommended dose [ 48 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, the increase of the ultimate strength was the same in both groups of chickens fed low-Zn diet irrespective of phytase inclusion. Our results agree with others, who report an influence of dietary Zn on the mechanical properties of bones [ 49 51 ]. On the other hand, there are studies showing that low-Zn diets do not increase bone breaking strength when compared to the Zn-deprived control [ 8 , 21 , 52 ] or group supplemented with ZnO at recommended dose [ 48 ].…”
Section: Discussionsupporting
confidence: 93%
“…These additionally available minerals could play a significant role in the synthesis of hormones of somatotropic axis which also could be responsible for a faster growth observed in broilers from the Zn25%+phyt group. It agrees with other studies showing a better growth and bone development in poultry after added phytase to the diet, irrespective of analyzed mineral elements [ 26 , 51 , 53 ].…”
Section: Discussionsupporting
confidence: 92%
“…The present study shows that dietary supplementation of 200 mg/kg Zn significantly increased the shear force of bone compared with the 300 mg/kg group. This result was similar to that of Stofanikova et al (2011) and Olgun and Yildiz (2017), who showed that bone biomechanical properties were affected by Zn supplementation in poultry. However, Swiatkiewicz and Koreleski (2008) indicated that supplementation of different levels of Zn had no effect on the mechanical characteristics of bone in laying hens.…”
Section: Resultssupporting
confidence: 90%
“…It is considered to be a coenzyme of more than 240 enzymes in birds’ bodies, and plays a major role in activating some antioxidant enzymes which sustain the defense system of avian body against reactive oxygen species [1,2,3]. The results of previous studies have indicated that Zn supplementation is important for enhancing the antioxidant capacity and improving the productive and reproductive performance [4,5,6,7], egg quality [8,9,10], and tibial quality [11,12,13] in laying hens and laying breeders. Reproductive performance, egg quality, tibial quality, antioxidant status, and tissue deposition are common variables employed in estimating the optimal dietary nutrient requirements for laying hens and breeders, following nonlinear regression models [6,14].…”
Section: Introductionmentioning
confidence: 99%